2010
DOI: 10.24084/repqj08.729
|View full text |Cite
|
Sign up to set email alerts
|

Stand-alone photovoltaic system for an emergency health clinic

Abstract: This paper presents a study and design of a complete stand-alone photovoltaic (PV) system for providing the electrical loads in an emergency health clinic according to their energy requirements. Typical energy consumption daily profiles for the four seasons are assumed. The PV system is optimally sized to be an optimal economic system. Homer software is used as the sizing and optimization tool to determine the size and specifications of photovoltaic system components, system cost and estimation of correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…15.095 kW/h. Hassan et al [50] proposed a stand-alone PV system to electrify an emergency health clinic in Egypt. The analysis including sizing, simulation, and economic assessment of the system showed that a 3.3 kW PV array and 20 batteries (6 V, 1156 Ah, 6.94 kWh) were needed to meet the total load of the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…15.095 kW/h. Hassan et al [50] proposed a stand-alone PV system to electrify an emergency health clinic in Egypt. The analysis including sizing, simulation, and economic assessment of the system showed that a 3.3 kW PV array and 20 batteries (6 V, 1156 Ah, 6.94 kWh) were needed to meet the total load of the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the new power and energy context such as greenhouse effect and other environmental issues, fuel depletion and electricity cost increase. New regulation and standards, telecom operators have to make efforts for using renewable energy solution [8].…”
Section: Case Studymentioning
confidence: 99%
“…Hybrid renewable power systems integrate two or more sources of energy, one of which is renewable, optionally a storage system and typically work in stand-alone mode [1], [2], [8]. To introduce renewable energy sources in hybrid power systems we also have to deal with the following disadvantages: renewable resources availability in different locations, intermittency, unpredictability, multiple economic and technical optimization criteria, unquantifiable environmental benefits, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, numerous researches discussed the techno-economic feasibility of hybrid renewable power systems [1][2][3][4][5][6] or PV power systems [7][8][9][10] using HOMER simulation tool. Techno-economic feasibility studies in the literature variated in their input data resources due to many climate databases available online.…”
Section: Introductionmentioning
confidence: 99%